Pancreatic Beta Cell in Health and Disease - Bell, Graeme I. (Springer, 2017)
Pancreatic Beta Cell and Insulin Biosynthesis -- Cell Signaling and Insulin Secretion -- Pancreatic Development and Beta-Cell Formation…